1997
DOI: 10.1103/physrevb.55.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the projector augmented-wave, pseudopotential, and linearized augmented-plane-wave formalisms for density-functional calculations of solids

Abstract: The projector augmented-wave ͑PAW͒ method was developed by Blöchl as a method to accurately and efficiently calculate the electronic structure of materials within the framework of density-functional theory. It contains the numerical advantages of pseudopotential calculations while retaining the physics of all-electron calculations, including the correct nodal behavior of the valence-electron wave functions and the ability to include upper core states in addition to valence states in the self-consistent iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(113 citation statements)
references
References 32 publications
1
106
0
Order By: Relevance
“…We use the first-principles PAW method [25][26][27] based on the DFT within the generalized gradient approximation (GGA).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We use the first-principles PAW method [25][26][27] based on the DFT within the generalized gradient approximation (GGA).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The PAW method has been implemented for plane waves by several groups. [27][28][29][30][31][32] We see the combination of real-space grid-based methods and the PAW method as an important step toward enabling larger calculations at a level of accuracy that is essentially all-electron in nature. There is a clear trend in electronic structure theory toward larger and more complex systems as for example nanostructures, large ͑bio-͒molecular complexes and extended defects in real materials-systems that all quickly challenge present-day high-accuracy DFT codes, which are typically limited to, at most, a few hundred atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent calculations using all-electron [22][23][24][25] and/or pseudopotentials 23-26 methods, coincide pointing out the trend of GGA's to enhance magnetism of magnetic materials and susceptibilities of non magnetic materials when compared with results from analogous LSDA calculations. Singh and Ashkenazi 22 using the all-electron FLAPW method confirmed that bulk V and Pd are correctly predicted as paramagnetic by the PW91 GGA approximation, but conclude also that GGA's do not have greater precision than the LSDA for studying transition metals (TM) and specially for magnetic materials.…”
Section: Introductionmentioning
confidence: 99%